2019
DOI: 10.1101/632422
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functional tunability from a distance: Rheostat positions influence allosteric coupling between two distant binding sites

Abstract: For protein mutagenesis, a common expectation is that important positions will behave like on/off "toggle" switches (i.e., a few substitutions act like wildtype, most abolish function).However, there exists another class of important positions that manifests a wide range of functional outcomes upon substitution: "rheostat" positions. Previously, we evaluated rheostat positions located near the allosteric binding sites for inhibitor alanine (Ala) and activator fructose-1,6bisphosphate (Fru-1,6-BP) in human live… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 7 publications
(58 citation statements)
references
References 18 publications
2
56
0
Order By: Relevance
“…hLPYK has many “functions.” We have developed a semi‐high throughput assay that can simultaneously characterize substrate affinity ( K a‐PEP for the substrate, phosphoenolpyruvate), binding of the allosteric inhibitor binding ( K ix ‐Ala for alanine), binding of the allosteric activator ( K ix ‐FBP for fructose‐1,6‐bisphosphate), allosteric coupling between the PEP and fructose‐1,6‐bisphosphate binding events ( Q ax ‐FBP ), and allosteric coupling between the PEP and Ala binding events ( Q ax ‐Ala ). By having a method that reports on many functions at once, we have found hLPYK to be a useful model to evaluate individual amino acid positions based on functional outcomes due to substitution 2,3 . In particular, our past studies have identified substitutions at nonconserved positions in and near the allosteric binding sites that modulated multiple functional parameters 2,3,5‐9 (Figure 1, green dots).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…hLPYK has many “functions.” We have developed a semi‐high throughput assay that can simultaneously characterize substrate affinity ( K a‐PEP for the substrate, phosphoenolpyruvate), binding of the allosteric inhibitor binding ( K ix ‐Ala for alanine), binding of the allosteric activator ( K ix ‐FBP for fructose‐1,6‐bisphosphate), allosteric coupling between the PEP and fructose‐1,6‐bisphosphate binding events ( Q ax ‐FBP ), and allosteric coupling between the PEP and Ala binding events ( Q ax ‐Ala ). By having a method that reports on many functions at once, we have found hLPYK to be a useful model to evaluate individual amino acid positions based on functional outcomes due to substitution 2,3 . In particular, our past studies have identified substitutions at nonconserved positions in and near the allosteric binding sites that modulated multiple functional parameters 2,3,5‐9 (Figure 1, green dots).…”
Section: Resultsmentioning
confidence: 99%
“…By having a method that reports on many functions at once, we have found hLPYK to be a useful model to evaluate individual amino acid positions based on functional outcomes due to substitution 2,3 . In particular, our past studies have identified substitutions at nonconserved positions in and near the allosteric binding sites that modulated multiple functional parameters 2,3,5‐9 (Figure 1, green dots).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations